The Mechanisms and Boundary Conditions of Drug Memory Reconsolidation - Chen, Liangpei; Yan, He; Wang, Yufang; He, Ziping; Leng, Qihao; Huang, Shihao; Wu, Feilong; Feng, Xiangyang; Yan, Jie (Frontiers in Neuroscience, 2021)
Drug addiction can be seen as a disorder of maladaptive learning and memory and is characterized by relapse. Therefore, disrupting drug related memories may be a potential way to destroy addiction. Pioneer studies over the last two decades have revealed that the consolidated memories are not static, but can be reconsolidated after retrieval, thereby providing candidate avenues for treatment of addiction. It is known that the limbic corticostriatal system play a vital role in encoding drug memory engram and different structures within it contribute differently to the process of memory reconsolidation, making it a potential target to prevent relapse. Besides, the molecular process is also active during memory reconsolidation, making it possible to destroy drug memories by amnestic agents. In this review, we put our eyes mainly on the brain structures that store drug memory engram, as well as molecular progress that involves in drug memory reconsolidation. Notably, we also have observed reports toward boundary conditions that constraint the therapeutic potential of memory reconsolidation. We discuss principles that would be employed for memory modifications. Finally, we emphasize the challenge of reconsolidation-based strategies, but end on an optimistic mind for the development of reconsolidation theory in drug relapse prevention.